2014
DOI: 10.1071/ch14426
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Berberine–INF55 (5-Nitro-2-phenylindole) Hybrid Antibacterials

Abstract: Berberine–INF55 hybrids are a promising class of antibacterials that combine berberine and the NorA multidrug resistance pump inhibitor INF55 (5-nitro-2-phenylindole) together in one molecule via a chemically stable linkage. Previous studies demonstrated the potential of these compounds for countering efflux-mediated antibacterial drug resistance but they didn’t establish whether the compounds function as originally intended, i.e. with the berberine moiety providing antibacterial activity and the attached INF5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The product was isolated by column chromatography (PE:EA = 5:1) as a light yellow solid (48.4 mg, 68%). Spectral data is consistent with previous reports …”
Section: Methodssupporting
confidence: 93%
“…The product was isolated by column chromatography (PE:EA = 5:1) as a light yellow solid (48.4 mg, 68%). Spectral data is consistent with previous reports …”
Section: Methodssupporting
confidence: 93%
“…In addition, structural simplification of the indole moiety turned out to be unfavorable for the antibacterial activity of hybrids, although it was shown that the indole nucleus is not necessary for NorA EPI . One may quickly conclude that berberine‐INF55 hybrids elicit their antibacterial effects through the combination of activities of two functionally distinct components (antibacterially active berberine and NorA inhibitor INF55), but a study suggests that the exact mechanism of action, in this case, differs from that when berberine is co‐administered with INF55‐based EPIs …”
Section: Efflux Pump Inhibitors Of Selected Clinically Relevant Pathomentioning
confidence: 99%
“…190 One may quickly conclude that berberine-INF55 hybrids elicit their antibacterial effects through the combination of activities of two functionally distinct components (antibacterially active berberine and NorA inhibitor INF55), but a study suggests that the exact mechanism of action, in this case, differs from that when berberine is co-administered with INF55-based EPIs. 191 To date, several potent indole-based NorA inhibitors were discovered and optimized, but their efficacy still needs to be evaluated in clinical settings.…”
Section: Aryl Alkenyl Amidesmentioning
confidence: 99%
“…Various derivatives of berberine have been developed and studied for their anti-hyperglycemic, anti-cancer, anti-inflammatory, anti-Alzheimer's disease and anti-microbial activities [19]. Derivatives with multidrug resistance pump inhibitory activity against Staphylococcus aureus [20] and that reduce fluconazole resistance against Candida albicans [21] have been reported. In addition, quaternary ammonium compounds inhibit the biofilm formation in P. aeruginosa and C. albicans have been reported [22].…”
Section: Introductionmentioning
confidence: 99%